The Ocean's labile DOC supply chain. Issue 5 (5th March 2022) - Moran, Mary Ann; Ferrer‐González, Frank X.; Fu, He; Nowinski, Brent; Olofsson, Malin; Powers, McKenzie A.; Schreier, Jeremy E.; Schroer, William F.; Smith, Christa B.; Uchimiya, Mario
Abstract: Microbes of the surface ocean release, consume, and exchange labile metabolites at time scales of minutes to days. The details of this important step in the global carbon cycle remain poorly resolved, largely due to the methodological challenges of studying a diverse pool of metabolites that are produced and consumed nearly simultaneously. In this perspective, a new compilation of published data builds on previous studies to obtain an updated estimate of the fraction of marine net primary production that passes through the labile dissolved organic carbon (DOC) pool. In agreement with previous studies, our data mining and modeling approaches hypothesize that about half of ocean net primary production is processed through the labile DOC pool. The fractional contributions from three major sources are estimated at 0.4 for living phytoplankton, 0.4 for dead and dying phytoplankton, and 0.2 for heterotrophic microbes and mesoplankton.